The Effect of Population Growth and Income Inequality on Poverty: Indonesian Case Study in the Development Context - Rowinna Siburian; Angela Anggraini; Kioko Tamba; Anju Christina; Adi Susanto Hasibuan (Outline Publisher, 2024)
This research aims to determine the relationship between population growth, income inequality and poverty in Indonesia. The research method used is a quantitative approach with panel data regression analysis. This data was obtained through the Central Statistics Agency (BPS) and processed using the EViews 12 application. The results of the analysis show that population growth has a significant negative influence on poverty, with a coefficient of -0.195 and a prob of 0.04). On the other hand, income inequality shows a significant positive effect on poverty with a coefficient of 18.558 and a probability of 0.001. Simultaneous hypothesis testing shows that the overall regression model is significant, with an F-statistic value of 11.879 (p = 0.000015). However, only 12.4% of the variation in poverty levels can be explained by population growth and income inequality, while 87.6% is explained by other factors not included in this study.